(untitled) (Research, Society and Development, 2022)
Introduction: The emergence of the pandemic caused by the new coronavirus has become one of the greatest challenges of the 21st century. The use of nanotechnology in textile fibers has the potential to become a resource for coping with the pandemic. In this field, fabrics impregnated with silver nanoparticles (AgNP) deserve to be highlighted, thanks to their antiviral and antibacterial attributes. Objectives: Thus, this integrative review aimed to evaluate its applications, antimicrobial efficacy, risks and regulation in order to contribute to the fight against the COVID-19 pandemic, as well as other infectious diseases. Methodology: To carry out this study, searches were carried out in the literature. Results and discussion: The results demonstrated that tissue-impregnated AgNPs can have wide application in the medical field. The literature also pointed out a relevant antimicrobial capacity of AgNPs, however this capacity seems to be related to their diameter and shape. Most nanomaterials are classified as GRAS, however this classification was made by extrapolating the data obtained in non-nanometric forms. In general, information on the bioavailability and toxicokinetics of nanomaterials is poorly known. In regulatory terms, despite recent advances, this is a topic still under discussion. Conclusions: Although there are still many regulatory gaps on the subject, the use of AgNP, not only in textile fibers, can become a valuable resource, not only for fighting the COVD-19 pandemic, but also for other diseases caused by microorganisms.